Double blind [compact disc, unabridged] - Johansen, Iris; Johansen, Roy (Johansen, Iris. Kendra Michaels series., 2018)
Kendra Michaels, formerly blind and now a hired gun for law enforcement agencies that rely on her sharp powers of observation, is reluctant to help the FBI with the most recent case they've brought to her. But then she hears the details: The body was found just blocks away from Kendra's condo. The young woman was carrying an envelope with Kendra's name on it, and inside was an SD card with what appears to be an innocuous video of a wedding reception. The woman died trying to get the video to Kendra, but for what purpose? Kendra joins forces with private investigator Jessie Mercado and agent-for-hire Adam Lynch to stop a killer whose nightmarish plan is slowly becoming clear.